International Production Networks and New Market Economies: Automobile Manufacturer Strategies in the CEECS - Richet, Xavier (Papeles del Este, 2005)
The present article analyzes the strategy implemented by international automobile industry majors in the Central and Eastern European countries that have just joined the European Union. It studies companies' reasons for investing in the area as part of their plans for internationalizing their production, as well as the consequences for the business fabric in each of the countries involved. Foremost among these are a series of technological and organizational innovations that have given rise to a new industrial scenario and a new division of labour between —old— and — new— Europe.